2019
DOI: 10.3390/ijerph16112009
|View full text |Cite
|
Sign up to set email alerts
|

Issue of Compliance with Use of Personal Protective Equipment among Wastewater Workers across the Southeast Region of the United States

Abstract: Wastewater workers are exposed to different occupational hazards such as chemicals, gases, viruses, and bacteria. Personal protective equipment (PPE) is a significant factor that can reduce or decrease the probability of an accident from hazardous exposures to chemicals and microbial contaminants. The purpose of this study was to examine wastewater worker’s beliefs and practices on wearing PPE through the integration of the Health Belief Model (HBM), identify the impact that management has on wastewater worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
(42 reference statements)
3
22
1
Order By: Relevance
“…Attitudes and normative issues positively explain farmers' intentions (Zeweld et al, 2017), while perceived usefulness and perceived ease of use are significant predictors of farmers' attitudes. These are similar to the constructs in the health belief model widely used to explain behaviour and attitude in various occupational settings for PPE compliance (Sim et al, 2014;Wright et al, 2019). Similar studies also use additional constructs such as the perceived adequacy of use, following Davis et al (1989).…”
Section: Applicable Theoretical Foundationmentioning
confidence: 78%
“…Attitudes and normative issues positively explain farmers' intentions (Zeweld et al, 2017), while perceived usefulness and perceived ease of use are significant predictors of farmers' attitudes. These are similar to the constructs in the health belief model widely used to explain behaviour and attitude in various occupational settings for PPE compliance (Sim et al, 2014;Wright et al, 2019). Similar studies also use additional constructs such as the perceived adequacy of use, following Davis et al (1989).…”
Section: Applicable Theoretical Foundationmentioning
confidence: 78%
“…In addition, wastewater and collection system workers should be surveyed about their existing PPE behaviors. For example, Wright et al recently surveyed wastewater workers in the southeastern United States to assess their beliefs about biological hazards and the influence of those beliefs on PPE practices (Wright et al, ). Although Wright et al found that workers generally were knowledgeable about the risks, implementation of some key types of PPE, particularly for preventing aerosol exposures, was low.…”
Section: Resultsmentioning
confidence: 99%
“…Interviewer-administered structured questionnaire was used to collect the required quantitative information on utilization and determinates of PPE use. Questionnaire was developed after review of similar literatures [11,14,15]. It includes socio-demographic characteristics of the workers, knowledge about PPE and occupational exposures, and seven HBM construct measures, namely, perceived susceptibility of occupational-related health problems, perceived severity of occupationalrelated health problems, perceived benefits of using PPE, perceived barriers to using PPE, perceived self-efficacy of using PPE, and cues to action of using PPE.…”
Section: Data Collection Methodmentioning
confidence: 99%